Infections in the Elderly Critically-Ill Patients - Esme, Mert; Topeli, Arzu; Yavuz, Burcu Balam; Akova, Murat (Frontiers in Medicine, 2019)
Infections are leading causes of morbidity and mortality in the advanced aged. Various factors including immunosenescence, comorbid chronic diseases and alterations in normal physiological organ functions may modify the frequency and severity of infections in the elderly patients. Normal body reactions to ensuing infection such as increased body temperature may be blunted in those patients and that may cause difficulties in differential diagnosis between infection and other diseases . Respiratory and urinary tracts are the most frequently involved systems in severe infections which may be accompanied by severe sepsis. Whereas bacteremia and sepsis are also associated with indwelling vascular catheters in elderly who is admitted to the intensive care unit. Patients with older age are more vulnerable to Clostridioides difficile infection, as well. Although the general management of infections in severely ill elderly patients are not different than younger ones, a meticulous care in fluid management and careful individualized optimisation in antibiotic therapy along with the other principals of antimicrobial stewardship are warranted in order to prevent increased mortality caused by infection. An organized team management when treating critically ill elderly patients in the ICU is essential and will reduce the morbidity and mortality due to infection in such patients.